Fiddle Tunes from Mississippi : Commercial and Informal Recordings, 1920-2018 - Bolick, Harry; Russell, Tony, 1946- (Book collections on Project MUSE., 2021)
"Beginning with Tony Russell's original mid-1970s fieldwork as a reference, and later working with Russell, Harry Bolick located and transcribed all of the Mississippi 78-rpm string band recordings. Some of the recording artists like the Leake County Revelers, Hoyt Ming and His Pep Steppers, and Narmour & Smith had been well known. Others, like the Collier Trio, were obscure. After multiple field trips the author located the descendants of the musicians. Previously unheard recordings and stories, unseen photographs and discoveries of nearly unknown fiddlers, such as Jabe Dillon, John Gatwood, Claude Kennedy, and Homer Grice, followed. The results are now available in this second, companion volume, Mississippi Fiddle Tunes: Commercial and Informal Recordings, 1920-2018. Two hundred and sixty-nine transcriptions of tunes supplement the biographies and photographs of the thirty-five artists documented here. Music comes from commercial recordings and small pressings of 78-rpm, 45-rpm, LP records, collector's field recordings, and the musicians' own home tape and disc recordings. Taken together, these two volumes represent a delightfully comprehensive survey of Mississippi's fiddle tunes"--